NUTRITION AS A STRATEGY FOR PREVENTING ALZHEIMER’S DISEASE - Raphae Almeida Ribeiro, Thiago; Caroline Chaves Queiroga Santos, Anne; Henrique Oliveira Macedo, Otávio; Borges Evangelista, Christiane; Carpegiane Ornelas Deles, Bruno; Ferreira Silva, Laércio; Silva Pereira, Alessandra; David Leite Santos, Leonardo; Guimarães da Silva, Aline; dos Santos Lins, Bárbara; Loreddany Santos Queiroz e Silva, Priscilla; Carolina de Souza Leite Santos, Ana; et al. (Health and Society, 2026)
This study aimed to investigate the relationship between diet and Alzheimer’s disease prevention, including dietary patterns and specific nutrients. An integrative literature review was conducted, analyzing articles retrieved from secondary databases such as the Virtual Health Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, and the Online System for Searching and Analyzing Medical Literature, using the descriptors “venomous animals,” “child,” and “adolescent,” and Boolean operators. Several studies have demonstrated that lifestyle factors play a central role in reducing the risk of developing Alzheimer’s disease or, at least, in delaying the onset of symptoms. One of these factors is nutrition, which significantly influences the risk of cognitive decline, dementia, and Alzheimer’s disease. One such dietary pattern is the Mediterranean diet, which plays a protective role in alterations in cognitive function, pre-dementia syndromes, and dementia, and therefore may represent an effective preventive strategy for Alzheimer’s disease, with low costs and few side effects. These promising preventive measures could yield important epidemiological data, which could translate into significant progress in public health.